Dynamic Molecular Modelling. The Case of Rearranging Polycyclic C8H9 Cations - Charles W. Jefford; Jiri Mareda; Jean-Jacques Combremont; Jacques Weber (CHIMIA)
The rearrangement of C8H9 polycyclic carbocations is represented by an animated graphic display using a calligraphic system. The chief feature is the interactive and three-dimensional visualization of the real-time evolution of the complex process. The advantages offered by computer graphics over conventional techniques are discussed.